From Biting to Hugging : Understanding Social Development in Infants and Toddlers. - Wittmer, Donna (Gryphon House Inc., 2018)
With the increase in both parents working outside the home during the last two decades, infants and toddlers are spending more time together in infant/toddler programs and family child-care homes. From Biting to Hugging will give you effective strategies to help you take advantage of this peer time.